Subcutaneous ICD combined with VT ablation for the secondary prevention of sudden cardiac death: pilot data from the prospective multinational SICD-VTAbl study. (14th October 2021) - Goldenberg, I; Maury, P; Sacher, F; Clementy, N; Huang, D T; Mulpuru, S; Friedman, P; Meyer, C; Benshushan, A D; Tiefenbrun, N L; Nof, E
Abstract: Background: The aim of the Subcutaneous ICD Combined with Ventricular Tachycardia Ablation (SICD-VTAbl) Study is to provide preliminary data on the safety and efficacy of a management strategy that incorporates S-ICD implantation and VT ablation among patients with a secondary prevention indication for an ICD. We hypothesize that VT ablation for the prevention of monomorphic VT recurrence combined with S-ICD implantation for termination of life-threatening VT/VF is safe, while reducing the need for device interventions and systemic complications associated with conventional transvenous ICD implantation for secondary prevention. Methods: SICD-VTAbl is an uncontrolled, prospective, multinational observational study, conducted in France, Germany, US (Rochester NY, and Rochester MN) and coordinated in Israel. We aim to prospectively enroll 30 patients presenting with scar-related VT/VF who will undergo VT ablation/substrate modification followed by S-ICD implantation. The primary endpoint is the first occurrence of S-ICD therapy (appropriate and inappropriate). Secondary endpoints include separate occurrence of appropriate and inappropriate ICD therapies, peri-procedural complications, and adverse clinical outcomes. Results: We provide clinical, arrhythmia, and outcome data on the first 15 patients enrolled in the SICD-VTAbl Study through February 2021. Mean age was 59±12 years, 78% were males, 60% had New York Heart Association (NYHA) Class ≥II symptoms, 20% had renal insufficiency, and 33% were treated with an antiarrhythmic medication (all amiodarone). Periprocedural, arrhythmia, and long-term outcome data are provided in Table 1. There were no major complications associated with the VT ablation and the S-ICD implantation procedures. During a median follow-up of 6 months (interquartile range: 2–12 months), 2 patients (13%) received S-ICD therapy: one patient (7%) experienced VF terminated by the S-ICD and one patient experienced a single episode of inappropriate S-ICD therapy. Adverse events during follow-up, unrelated to study procedures, occurred in 3 patients (20%): hospitalization for heart failure exacerbation (N=1) and non-cardiovascular hospitalizations (N=2). None of the patients died during follow-up (Table 1). Conclusions: Our preliminary data from the SICD-VTAbl Study suggest that a management approach that incorporates VT ablation followed by S-ICD implantation is safe and may lead to improved arrhythmia and clinical outcomes in patients presenting with a secondary prevention indication for an ICD. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Research grant to Sheba Medical Center from Boston Scientific